2020
DOI: 10.1038/s41598-020-76991-6
|View full text |Cite
|
Sign up to set email alerts
|

Salivary microbiome composition changes after bariatric surgery

Abstract: Recent studies show that the salivary microbiome in subjects with obesity differ from those without obesity, but the mechanism of interaction between the salivary microbiome composition and body weight is unclear. Herein we investigate this relation by analyzing saliva samples from 35 adult patients with obesity undergoing bariatric surgery. Our aim was to describe salivary microbiome changes during body weight loss on an individual-specific level, and to elucidate the effect of bariatric surgery on the saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 51 publications
(61 reference statements)
2
25
0
1
Order By: Relevance
“…Among a line of other genera significantly increased in MUO in the present study, Granulicatella is known to decrease in the oral cavity of obese patients after the metabolic surgery 27 , and Oribacterium has been reported as a potential obesogenic bacteria 28 . On the other hand, Succinivibrio , a bacterium known to correlate with risk of type 2 diabetes and obesity disease 29 was significantly correlated with plasma fasting insulin, HOMA-R, TG, BMI, weight, waist circumference, and HbA1c in present study.…”
Section: Discussionsupporting
confidence: 55%
“…Among a line of other genera significantly increased in MUO in the present study, Granulicatella is known to decrease in the oral cavity of obese patients after the metabolic surgery 27 , and Oribacterium has been reported as a potential obesogenic bacteria 28 . On the other hand, Succinivibrio , a bacterium known to correlate with risk of type 2 diabetes and obesity disease 29 was significantly correlated with plasma fasting insulin, HOMA-R, TG, BMI, weight, waist circumference, and HbA1c in present study.…”
Section: Discussionsupporting
confidence: 55%
“…The diseases associated with oral microorganisms involve multiple systems, including the cardiovascular system, digestive system, endocrine system, and other systems. For example, the salivary microbiome of obese patients differs from that of normal-weight hosts, and also changes during the period of weight loss (Džunková et al, 2020). However, it remains unclear whether the dietary changes or obesity itself affects the microbiome.…”
Section: Disease Statesmentioning
confidence: 99%
“…25 The Weightloss Surgery and Oral Microflora Adawi et al Weightloss Surgery and Oral Microflora Adawi et al cumulative number of female participants was higher, and they contributed to 72.9% (290) of the cumulative sample size (398), whereas male participants contributed only 27.1% (108). The mean age of participants ranged from 33.9 27 to 48 26 years, with variation in each study. Four out of seven studies reported the presence of comorbidities in the selected participants (DM, hypertension, and others) 15,16,26,28,33 ; in one study, none of the participants had comorbidities, 26 whereas two studies did not disclose these details.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…13,25 With regard to relevant oral findings, two studies reported the presence of periodontitis in sample groups, 13,25 two studies mentioned that there was no periodontitis 16,27 ; in one study, participants were wearing removable dental prosthesis and had dental caries, 15 whereas two studies did not disclose any of these details. 26,28,32 There was a difference in the type of BS used in the selected studies. RYGB 13,15,16,25 was performed in four out of seven studies, in one study, SG was the choice of the surgical technique, 28 four different types of BS procedures were performed in one study on the selected population, 26 whereas one study did not give details about the type of weight loss surgery.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation